Iran, Tabrīz. Das ilkhanidische Tabrīz: Bauforscherische und archäologische Untersuchungen zum Rabʿ-i Rashīdī. Die Arbeiten des Jahres 2018 - Fuchs, Christian; Heidenreich, Anja (e-Forschungsberichte des DAI, 2019)
The ongoing activities at the citadel of Rabʿ-e Rashīdī in Tabriz, mutually developed between Iranian and German Institutions, were extended by a further collaboration with the University of Bamberg that will focus the Ilkhanid remains in Tabriz. The works brought a more complex stratigraphy and building history than previously thought: The eastern gate was built at a later stage than the fortification wall, or that it was substantially altered, by inserting extensive portions of brick into the extant mudbrick wall. The fresh-water conducts found under the eastern entrance are matching with written sources on the importance of water installations at the Rabʿ-e Rashīdī from both, the Ilkhanidic foundation and the Qajar period.